(untitled) (Applied Biological Research, 2024)
Obesity, a global health challenge, particularly affecting Asian populations due to inappropriate snacking behaviour and food choices, prompted this study. The research aimed to evaluate the impact of a 10-week cognitive group treatment on snacking behaviour among overweight women aged 30-60 years. In a randomized control trial with 66 female working participants (BMI > 25 kg m-²), the groups were categorized as control (n = 34) and experimental (n = 32). Initially, snacking contributed significantly to daily energy (29.39%), carbohydrates (21.11%), protein (35.53%), and fat (50.61%) intake in the experimental group. After the cognitive group treatment, there was a substantial (p≤0.01) reduction in the contribution of these nutrients through snacking, with percentages dropping to 11.62, 14.60, 10.04, and 7.67, respectively. Post-treatment, significant (p≤0.01) reductions were observed in body weight (4%), fat mass (2%), waist circumference (4.9%), and hip circumference (2.7%) among the subjects. The study emphasized that the behavioural changes leading to healthier snacking can be a sustainable approach for weight management and that making healthier snack choices can aid in the battle against overweight and obesity.